Sistem Informasi Inventori Bahan Baku Obat Berbasis Web Pada PT Nano Herbaltama Internasional - Syahrul Aminudin Alfariz; Muhammad Cordiaz (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The Drug Raw Material Inventory Information System at PT Nano Herbaltama Internasional was created and implemented in the form of a web-based application, making it easier for PT. Nano Herbaltama Internasional especially the leaders, admins, and staff in managing the storage of raw materials. Applications made in the manufacture of this system use the PHP, MySql, and Lavarel programming languages. The purpose of making this application is to make it easier for leaders to monitor the management of special medicinal raw materials to admin and warehouse staff in receiving incoming raw materials, issuing raw materials and monitoring raw material stocks.